Detection of Mycoplasma gallinarum by Real-Time PCR - Leigh, S.A.; Evans, J.D. (International Journal of Poultry Science, 2009)
Mycoplasma gallinarum colonizes poultry as well as mammals, but is considered to have a commensal relationship with its hosts. Though unable to cause poultry disease by its self, reports have been published suggesting a synergism during mixed infections between M. gallinarum and respiratory viruses or their vaccine strains that can precipitate airsacculitis. Currently, little research is being done on M. gallinarum and little is known about its carrier rate in chickens and other poultry. Two primer sets were tested for their ability to detect M. gallinarum using real-time PCR. One set published by Lauerman amplifies a fragment from the M. gallinarum 16S ribosomal DNA sequence. The other set (101-2) was developed in this laboratory and amplifies a short segment of DNA that appears to be unique to some strains of M. gallinarum. The Lauerman primer set is specific for M. gallinarum and has a detection limit of 100 genomes. The 101-2 primer set is specific for some strains of M. gallinarum, although, it is 100-fold less sensitive than the Lauerman primer set. The 101-2 primer set appears to be unsuited for M. gallinarum detection, but it does provide a method of differentiating M. gallinarum strains by PCR. These primer sets provide a means to rapidly determine the M. gallinarum carrier status of flocks by real-time PCR and will help in identifying M. gallinarum in mixed infections.